Thinking Ahead: Incremental Language Processing is Associated with Receptive Language Abilities in Preschoolers with Autism Spectrum Disorder. - Venker, Courtney E.; Edwards, Jan; Saffran, Jenny R.; Ellis Weismer, Susan (Journal of Autism & Developmental Disorders, 2019)
In typical development, listeners can use semantic content of verbs to facilitate incremental language processing—a skill that is associated with existing language skills. Studies of children with ASD have not identified an association between incremental language processing in semantically-constraining contexts and language skills, perhaps because participants were adolescents and/or children with strong language skills. This study examined incremental language processing and receptive language in young children with ASD with a range of language skills. Children showed a head start when presented with semantically-constraining verbs (e.g., Read the book) compared to neutral verbs (e.g., Find the book). Children with weaker receptive language showed a smaller head start than children with stronger receptive language skills, suggesting continuity between typical development and ASD.